Effect of copper on the growth and photochemical properties of lanthanum manganite film electrode - Pan, G.T.; Chong, S.; Yang, T.C.K.; Shukla, P.; Chiu, W.S.; Juan, J.C. (Elsevier, 2017)
This study demonstrates that p-type copper-doped lanthanum manganite (LaMnO3) film on aluminum plate substrate is a stable and efficient photo-absorber for hydrogen collection from water. Compared to using photocatalyst powder, thin-film reactor is a convenient method for industrial applications as no further filtration process is required. The copper-doped LaMnO3 semiconductor films were readily deposited on aluminum plate substrates via sol-gel approach as well as spin-coating technology using photoelectrochemical cathodic current under AM 1.5 G illumination (100 mW/cm2). The influences of copper loading on LaMnO3 films in terms of surface and internal pore structure, morphology, optical and photoelectrochemical properties were comprehensively investigated. The bandgap energy and carrier density of the copper-doped LaMnO3 films were found to range between 2.670–2.677 eV and 4.80 × 1015–6.18 × 1015 cm−3, respectively. The flat band potentials of these films lied in the range of −0.424 to +0.067 V vs. Ag/AgCl electrode (or −0.217 to +0.232 V vs. NHE) based on the Mott-Schottky measurements. When the molar ratio of copper in the reaction solution was higher than 0.6, the copper-doped LaMnO3 film possessed the characteristics of a p-type semiconductor and yielded the best photo-performance when compared to n-type semiconductor films.